Thinking outside the box: Axillary to superior mesenteric artery bypass for chronic mesenteric ischemia - Austin R. Nelson, MD; Justin M. Robbins, MD; Jonathan Velasco, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Endovascular and open approaches are available for patients with chronic mesenteric ischemia. Axillary to superior mesenteric artery bypass has been described sparsely in the vascular literature. We describe a successful axillary to superior mesenteric artery bypass in an 84-year-old female patient with extensive aortoiliac disease precluding traditional approaches and performed in a community vascular surgery setting.